Permian Basin Oil and Gas Recovery Conference 1994
DOI: 10.2118/27677-ms
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Huff 'n' Puff Field Case: Five-Year Program Update

Abstract: CO2 Huff 'N' Puff has been used on a shallow light oil field to add value to existing oil producing wells by increasing the ultimate oil recovery. Testing was initiated in 1985 with a more continuous program starting in 1989. The application of CO2 Huff 'N' Puff has increased oil production 180,000 bbls above the primary recovery with the use of 210 MMCF (12,200 tons). The CO2 treatments have been relatively small with 390 treatments performed on 240 wells. Introduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…In this technique, after the injection of CO 2 into the reservoir, the well would be shut in for a predetermined period of time (i.e., soaking period) depending on the reservoir conditions (i.e., reservoir rock and fluid properties). , Then the oil production initiates by converting the injection well to a producer. The injected CO 2 has the ability to change and modify the reservoir rock and fluid properties, ending up enhancing the oil recovery process. , Mechanisms contributing to increased oil recovery in the huff-and-puff process include oil viscosity reduction, oil swelling due to dissolution of gas in crude oil, solution gas drive aided by gravity drainage in thick reservoirs, vaporization of lighter components of oil, interfacial tension reduction, and relative permeability effects. …”
Section: Introductionmentioning
confidence: 99%
“…In this technique, after the injection of CO 2 into the reservoir, the well would be shut in for a predetermined period of time (i.e., soaking period) depending on the reservoir conditions (i.e., reservoir rock and fluid properties). , Then the oil production initiates by converting the injection well to a producer. The injected CO 2 has the ability to change and modify the reservoir rock and fluid properties, ending up enhancing the oil recovery process. , Mechanisms contributing to increased oil recovery in the huff-and-puff process include oil viscosity reduction, oil swelling due to dissolution of gas in crude oil, solution gas drive aided by gravity drainage in thick reservoirs, vaporization of lighter components of oil, interfacial tension reduction, and relative permeability effects. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to determine the effect of different operating parameters on the performance of the cyclic CO 2 injection process. Additional studies on the performance of some field-scale cyclic CO 2 injection in USA (e.g., Paradis, West Cote, Timbalier, Magnet, Picket Ridge, and Thompson, Bati field projects) revealed that the presence of a gas cap, gravity segregation, and a higher remaining oil saturation can improve the recovery of the cyclic injection process. Furthermore, changes in gas–oil relative permeability curves may support the oil production near the well-bore. Further studies on the effect of CO 2 slug size also revealed that a higher volume of CO 2 injected into the reservoir is able to recover more oil under some specific conditions during the cyclic injection process. , It has also been reported that the cyclic CO 2 injection process profited by lower crude oil viscosity since the diffusion of CO 2 into the oil is accelerated . Experimental study on the cyclic injection of mixtures of CO 2 with hydrocarbon and flue gases also showed that such mixtures increase the oil recovery if they are injected in a particular range of volumetric ratio. A laboratory and field evaluation of the cyclic CO 2 injection process indicated that a high permeability of the reservoir rock as well as viscous fingering phenomena plays a positive role in the recovery efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 utilization for 0.15PV is 0.431Mscf/STB. The CO 2 utilization achieved in this study seems to be more favorable than those of some field treatments (Brock and Bryan, 1989;Haskin and Alston, 1989;Thomas and Monger-McClure, 1991;Miller et al, 1994) since CO 2 huff 'n' puff process is more successful in pressure-depleted reservoirs than in water-drive reservoirs (Monger-McClure et al, 1991). Figure 5 can also be used to examine the role of slug size in CO 2 huff 'n puff process.…”
Section: Effects Of Slug Sizementioning
confidence: 73%